2019
DOI: 10.1093/ndt/gfz169
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NLRP6 expression increases the severity of acute kidney injury

Abstract: Background Nlrp6 is a nucleotide-binding oligomerization domain-like receptor (NLR) that forms atypical inflammasomes. Nlrp6 modulates the gut epithelium interaction with the microbiota. However, the expression and function of Nlrp6 in the kidney, a sterile environment, have not been characterized. We explored the role of Nlrp6 in acute kidney injury (AKI). Methods In a transcriptomics array of murine nephrotoxic AKI, Nlrp6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…PGC-1α is encoded by the PPARGC1A gene and belongs to the PGC-1 family, also composed of PGC-1β (encoded by PPARGC1B), which contributes to maintain basal mitochondrial function, and PRC (PGC-1-related coactivator, encoded by PPRC1), which appears to be restricted to regulating mitochondrial biogenesis in proliferating cells [24] ( Figure 1A). While there is abundant literature on PGC-1α and kidney disease, as discussed below, much less is known about the role of PGC-1β and PRC in kidney disease, despite the fact that transcriptomic studies have identified them as differentially expressed during experimental AKI [25][26][27] (Figure 1B). [28].…”
Section: Pgc-1α: a Regulator Of Mitochondrial Biogenesismentioning
confidence: 99%
“…PGC-1α is encoded by the PPARGC1A gene and belongs to the PGC-1 family, also composed of PGC-1β (encoded by PPARGC1B), which contributes to maintain basal mitochondrial function, and PRC (PGC-1-related coactivator, encoded by PPRC1), which appears to be restricted to regulating mitochondrial biogenesis in proliferating cells [24] ( Figure 1A). While there is abundant literature on PGC-1α and kidney disease, as discussed below, much less is known about the role of PGC-1β and PRC in kidney disease, despite the fact that transcriptomic studies have identified them as differentially expressed during experimental AKI [25][26][27] (Figure 1B). [28].…”
Section: Pgc-1α: a Regulator Of Mitochondrial Biogenesismentioning
confidence: 99%
“…In the lung, Nlrp6 ‐deficient mice are more resistant to pulmonary Staphylococcus aureus infection compared with WT counterparts, and this protective effect is mediated by enhanced neutrophil recruitment and neutrophil‐associated bacterial clearance following infection 28 . Nlrp6 is also expressed in the tubular epithelium of healthy murine and human kidneys, and its expression is reduced upon acute kidney injury induced by folate acid or cisplatin overdose, in both human or mouse models 62 . Furthermore, deficiency of Nlrp6 in mice aggravates the severity of nephrotoxic acute kidney injury, characterized by enhanced apoptotic and pro‐inflammatory responses in the tubular cells, suggesting a nephroprotective role of NLRP6 in acute kidney injury 62 .…”
Section: Nlrp6 Inflammasome Assembly Regulation and Effector Functionmentioning
confidence: 99%
“…Nlrp6 is also expressed in the tubular epithelium of healthy murine and human kidneys, and its expression is reduced upon acute kidney injury induced by folate acid or cisplatin overdose, in both human or mouse models 62 . Furthermore, deficiency of Nlrp6 in mice aggravates the severity of nephrotoxic acute kidney injury, characterized by enhanced apoptotic and pro‐inflammatory responses in the tubular cells, suggesting a nephroprotective role of NLRP6 in acute kidney injury 62 . Taken together, the complicated and multifaceted functions of NLRP6 in regulating disease associated with a multitude of organs warrant a continued thorough investigation.…”
Section: Nlrp6 Inflammasome Assembly Regulation and Effector Functionmentioning
confidence: 99%
“…Blots were washed with PBS/Tween and subsequently incubated with appropriate horseradish peroxidase-conjugated secondary antibody (1:2000, Amersham, Aylesbury, UK). After washing, blots were developed with the chemiluminescence method (ECL, Amersham, UK), and then probed with the mouse monoclonal anti-α-tubulin antibody (1:5000, Sigma, St, Louis, MO, USA) [32]. Levels of expression were corrected for minor differences in loading.…”
Section: Western Blotmentioning
confidence: 99%